A decade of diving: responses of Cassin’s auklets to variable foraging conditions in the California Current System - Karnovsky, Nina J.; Warzybok, Pete; Cavalcanti, Andre; Hardin, Johanna; Brown, Zachary W.; Caves, Eleanor; Flynn, Clare M.; Gallaher, Gail; McDuffie, Nicole; McOmber, Kristina; Bradley, Russell W.; Elliott, Meredith L.; et al. (Frontiers in Bird Science, 2025)
We investigated how a planktivorous seabird adjusts its foraging behavior in response to different levels of prey biomass. We studied the diving behavior of Cassin’s auklets (Ptychoramphus aleuticus) breeding on Southeast Farallon Island and feeding in the highly variable California Current System. In recent years Cassin’s auklets have experienced mass mortality events and complete reproductive failure due to anomalous atmospheric and oceanographic conditions. We hypothesized that in years with low prey biomass, Cassin’s auklets work harder to collect food for themselves and for their chick and that reproductive success is lower during those years. To test this hypothesis, we equipped 133 Cassin’s auklets with Time Depth Recorders from 2008 – 2017. We estimated krill biomass levels in the top 30 m during oceanographic cruises carried out where Cassin’s auklets foraged. We measured the annual number of chicks fledged per pair. In years with high prey biomass reproductive success was very high and Cassin’s auklets collected prey in fewer, deeper and longer dives. They spent more time in the bottom of their dives and more time underwater. When krill biomass was low, they made shallow, shorter dives and a higher number of these dives during their foraging trips. Variability in the California Current System greatly influenced the diving behavior and reproductive success of the Cassin’s auklets. Climate anomalies that lead to extremely low krill biomass are expected to become more frequent. Cassin’s auklets are likely not going to able to increase their foraging effort enough to be able to survive and reproduce.